Effects of oxidation states of Copper (Cu), Nickel (Ni), Palladium (Pd) and Silver (Ag) on rejection by nanofiltration membranes - Brooms, Thabo John (My University, 2011)
Mining industry produces metals which are economical and serve as high valuable commodities in South Africa. This country is regarded as the world leading producer of precious metals such as platinum group metals (PGMs). Silver (Ag), which is also a precious metal, contribute to the country’s economy wealth due to its significance during industrial applications. Base metals such as copper (Cu) and nickel (Ni), though they are low valued, play a significant role in the republics economic wealth. Mining wastewater contains some of these metals, which end up polluting the environment. A possibility to recover this was investigated using NF membranes. Mine effluent was simulated by using relevant reagents. Characterization of NF90, NF- and NF270 membranes, was done by using scanning electron microscopy (SEM), clean water permeability, single charged salts of NaCl and MgCl2 and binary mixture of NaCl/MgCl2 studies. All the rejection experiments were conducted at pH 2.0 with varying pressure and concentrations. Flux measurements indicated that water permeability through the membranes trend, NF270 > NF90 > NF-. The experiments were performed at pressures of 5 bar, 10 bar, 15 bar and 20 bar. For NF90 membrane, a rejection of Na+ monovalent ion in 20 ppm solution was less than of Mg2+ (divalent) ion. Percentage rejections of 90% (Na+) and 98% (Mg2+) were achieved. NF- had rejection of 83% and 90% for Na+ and Mg2+, respectively. In the case of NF270, the membrane had rejection of 92% (Na+) and 94% (Mg2+), respectively. At 100 ppm, all three membranes showed a decreasing trend in rejection while increasing pressure. For binary-solution mixture, Mg2+ ion still had the highest rejection compared to Na+ ion with about 94% and 85% on NF90 than on NF270 and NF-. The high rejection of divalent ion as compared to monovalent ion for charged solutes was due to solute size and electrostatic interaction between the membrane surface layer and the solute. In the case of transition metal rejection studies, Pd2+ ion had an average of 90%, with Ni2+ ion ≈ 95% and Cu2+ ion ≈ 98% as single salts on NF90 compared to NF270 and NF-. However, as for binary and trinary solution mixture, the competition amongst ions was high, where Pd2+ ion rejection was ≈ 99,0%, while Ni2+ and Cu2+ ions was > 90% on NF90 and NF-. Therefore it was excluded from the tests. For the monovalent metal ions (Ag+ and Cu+), the rejection was > 90% in almost all concentrations mixtures. During membrane fouling evaluation, AgCl salt fouled the most, compared to other metal ions, forming a concentration polarization accumulation on the membrane surface for both 20 and 100 ppm solutions. This situation leads to cake layer formation which causes a flux decline, reduces membrane life time and lowers the rejection performance of NF membranes. The aim of this study was to evaluate the performance of three commercial polymeric membranes (NF90, NF270 and NF-) during rejection of the metal
Thesis (M. Tech.(Chemistry)--Vaal University of Technology)), 2010
Keywords: Mine wastewater - recovery of metals; Copper; Nickel; Palladium; Nanofiltration membranes; Commercial polymeric membranes; Metal recovery - mine wastewater; Mining - South Africa; Base metals - recovery; 660.284245; Water reuse; Water - Purification - Filtration; Copper - Oxidation; Nickel; Palladium; Silver